Analisis Kinerja Dinas Perhubungan Komunikasi dan Informatika (Studi Kasus Pada Unit Pelaksana Teknis Dinas Perparkiran Kota Surakarta) - Sentot Darmodjo; Dyah Hariani; Hesti Lestari (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
Technical unit dept. parking surakarta city who acts as management parking surakarta should have a good performance in order the parking management surakarta city. It was because still many problems caused by the parking itself.Technical unit dept. parking city surakarta is agency which give responsibility to transportation agency head communication and informatics surakarta city.Research aims to tell performance transportation department communication and informatics uptd parking surakarta city and for identifies factors support and hinder performance transportation department communication and informatics Surakarta city.In this research researchers used method research qualitative spatially descriptive, thus data collected shaped words, its picture instead figures.The data covering transkip the interview, notes field, photos, personal document and others.The result of this research showed that performance transportation department communication and informatics technical unit basic parking surakarta city overall can be said to have went on quite well and in terms of factors support the performance of technical unit basic parking surakarta city among others management policies, management of human resources technology, culture organization, leadership.While factor that inhibits performance technical unit basic parking surakarta city is organizational structure, incentives given special for employees who for achievement and there is still employees who do not control science tehnologi.